A phase I study to evaluate the safety, tolerability, and pharmacokinetics of HEC113995PA·H2O, a novel dual-acting serotonergic antidepressant, in healthy subjects - Wu, Xue; Wu, Qingqing; Ding, Qichen; Zhuang, Yulei; Luo, Lin; Zhang, Yingjun; Deng, Li; Jin, Chuanfei; Li, Xue; Huang, Zhangma; Qin, Haiping; Xin, Liang; et al. (Frontiers in Pharmacology, 2025)
PurposeHEC113995PA·H2O is a novel, potent and selective serotonin (5-HT) reuptake inhibitor and a 5-HT1A receptor partial agonist, and thus is categorized as a serotonin partial agonist-reuptake inhibitor. The objective of this study was to evaluate the safety, tolerability, and pharmacokinetics of HEC113995PA·H2O in healthy subjects after single and multiple dosing, as well as the food effect on pharmacokinetics and safety of HEC113995PA·H2O.MethodsThe entire study was comprised of three parts: Part I (single ascending-dose study), Part II (food effect study), and Part III (multiple ascending-dose study). A total of 121 healthy subjects were enrolled in the study. HEC113995PA·H2O tablet or placebo was administered per protocol requirements. Blood samples were collected at the designated time points for pharmacokinetic analysis. Safety was assessed by clinical examinations and adverse events.ResultsIn Part I, AUC and Cmax were found to by and large linear within the 2.5–80 mg dose range. t1/2 of HEC113995PA·H2O was 27.17∼38.58 h. In Part II, we revealed that HEC113995PA·H2O administration post meal could increase Cmax and AUC0-t. In Part III, multiple administration led to accumulated body exposure and the PK of healthy subjects reached a steady state after 7 days of continuous administration in each dose group.ConclusionHEC113995PA·H2O was safe and generally well-tolerated in healthy subjects. Based on the pharmacokinetic and safety data mentioned above, we expect that postprandial administration will favorably increase drug concentrations in the body and reduce gastrointestinal adverse events.